2017
DOI: 10.18632/oncotarget.20733
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacometabolomics identifies dodecanamide and leukotriene B4 dimethylamide as a predictor of chemosensitivity for patients with acute myeloid leukemia treated with cytarabine and anthracycline

Abstract: Clinical responses to standard cytarabine plus anthracycline regimen in acute myeloid leukemia (AML) are heterogeneous and there is an unmet need for biological predictors of response to this regimen. Here, we applied a pharmacometabolomics approach to identify potential biomarkers associated with response to this regimen in AML patients. Based on clinical response the enrolled 82 patients were subdivided into two groups: complete remission(CR) responders (n=42) and non-responders (n=40). Metabolic profiles of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Of particular interest were also metabolites with a role in altered lipid and fatty acid metabolism associated with respect to doxorubicin chemosensitivity (low levels of LysoPC 16:1 and high levels of glycerol in doxorubicin resistant AML cell lines). Alterations to lipid metabolism are a common feature across multiple cancer types (41)(42)(43)(44)(45)(46), and a growing number of studies have shown its importance for AML as well (7,(47)(48)(49). One of the key alterations to lipid metabolism in AML is an increased dependence on lipid catabolism through fatty acid oxidation (FAO).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest were also metabolites with a role in altered lipid and fatty acid metabolism associated with respect to doxorubicin chemosensitivity (low levels of LysoPC 16:1 and high levels of glycerol in doxorubicin resistant AML cell lines). Alterations to lipid metabolism are a common feature across multiple cancer types (41)(42)(43)(44)(45)(46), and a growing number of studies have shown its importance for AML as well (7,(47)(48)(49). One of the key alterations to lipid metabolism in AML is an increased dependence on lipid catabolism through fatty acid oxidation (FAO).…”
Section: Discussionmentioning
confidence: 99%
“…The growing field of metabolomics and its approaches allows full metabolic profile evaluation in AML patients and leukemic cell cultures to explore the relationship between metabolism and resistance. Metabolomics studies of leukemia cell lines have been targeted to an identify metabolic pathways of resistance in multiple forms of leukemia (6)(7)(8). One study specifically investigating chemo-sensitivity has further explored the alterations to glutamine, glucose, fatty acid metabolism, and oxidative phosphorylation in cells resistant to commonly used chemotherapy (9).…”
Section: Introductionmentioning
confidence: 99%
“…Variable Importance in Projection (VIP) scores will be used to rank metabolites by their discriminating importance and metabolites with VIP score >1 (standard for untargeted metabolomics studies) will be identified as candidates. [74][75][76][77] Candidate metabolites will be subjected to multivariate analysis to exclude possible confounding with other clinical/ patient characteristics. Subsequently, a nested case-control approach will be used for quantitative metabolomics analysis to measure the absolute concentration of candidate metabolites on 120 repeated samples (60 adults, 60 children) from the discovery cohort (n = 20 no AKI, n = 20 KDIGO AKI, n = 20 NCI AKI).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic profiling by ultra-high performance liquid-chromatography mass spectrometry was used to study the metabolome of FLT3-ITD positive AML [77], which until now has been poorly understood. Using ultra-high performance liquid-chromatographymass spectrometry, they identified a specific metabolomic signature in plasma and in leukemic cells according to FLT3 status, including lysophospholipid metabolism, cysteine/methionine metabolism, tryptophan metabolism, purine metabolism and biosynthesis and carnitine mediated fatty acid oxidation [77][78][79][80].…”
Section: Systemic Metabolomic Profiling: the New Era Of Personalized Medicinementioning
confidence: 99%